Рsychological and Technological Bases of the Process of Learning Optimization - Zoryana Koval’chuk (Pedagogical Discourse, 2012)
Рsychological and technological features of the process of study optimization are revealed by the author of the article. It is indicated that they are designed to create optimal conditions for the solution of practical problems and is a process of complex influence onto the personality of the student. Using innovative learning technologies, to the author’s opinion, requires such an organization of the pedagogical process, where the main isn‘t formal mastering of knowledge and skills, but the search of options for solving problems, analyzing of the alternatives.